Modelling of membrane bonding response: part 1 development of an adhesive contact interface element. Issue 3 (23rd February 2022) - Liu, Xueyan; Kasbergen, Cor; Li, Jinlong; Scarpas, Tom
ABSTRACT: The adhesive bonding strength of the membrane layers between the asphalt concrete surface layers and the decks of steel bridges has a strong influence on the fatigue life of orthotropic steel deck bridges (OSDBs). The most important requirement for the application of membrane materials to orthotropic steel deck bridges is that the membrane adhesive layer is able to sufficiently bond to its surrounding material layers. The interfacial properties between the membrane and the layers bonded to it have not been extensively studied in the current orthotropic steel deck bridge system. In this paper, details of the contact interface element utilised to model the interfacial bonding properties will be discussed. Furthermore, the traction-separation material law will be chosen to describe the bonding response of the interfacial properties of the membrane to its surrounding surfacing layers on OSDBs. Some numerical examples, in which various aspects of the finite elements response of the contact interface model will be presented. Utilisation of the model in finite element analyses has enabled the investigation of the response of a 3D orthotropic steel deck bridge subjected to the different traffic loading conditions.